Pulmonary Rehabilitation Only Versus With Nutritional Supplementation in Patients With Bronchiectasis: A RANDOMIZED CONTROLLED TRIAL. Issue 6 (November 2018) - Doña, Esperanza; Olveira, Casilda; Palenque, Francisco Javier; Porras, Nuria; Dorado, Antonio; Martín-Valero, Rocío; Godoy, Ana M.; Espildora, Francisco; Olveira, Gabriel
Abstract : Purpose: Pulmonary rehabilitation (PR) is recommended for bronchiectasis, but there is little evidence of its efficacy in these patients. The aim of this study was to assess the effect of PR in normally nourished patients with noncystic fibrosis bronchiectasis compared with the effect of PR plus an oral nutritional supplement (PRONS). Methods: A single-center randomized controlled trial, parallel treatment design in which participants were randomly assigned to receive PR for 12 wk or PR plus a high-protein nutritional supplement enriched with beta-hydroxy-beta-methylbutyrate. Outcome assessments were performed at baseline, 12 and 24 wk including cardiopulmonary exercise testing, health-related quality of life (HRQOL), bronchorrhea, dyspnea, psychological symptoms, spirometry, and exacerbations. Results: Thirty patients were randomized into 2 groups of 15 participants. In both groups, cardiopulmonary exercise testing, HRQOL, dyspnea, and spirometry parameters significantly increased from baseline at 3 and/or 6 mo. Conclusion: PR improved exercise capacity, HRQOL, and respiratory parameters. The use of PRONS did not have a significant effect on the results. Abstract : Guidelines for the treatment of noncystic fibrosis bronchiectasis recommend incorporating pulmonary rehabilitation (PR). Thirty participants were randomly assigned to receive PR for 12 wk or PR plus an oral nutritional supplement. It was observed that PR significantly improved exercise capacity, quality of life, and respiratory parameters without significant differences between groups.